Paul before the Areopagus and other New Testament studies - Stonehouse, Ned Bernard, 1902-1962 (London, UK Tyndale, 1951)
Includes bibliographical references.
Keywords: Paul, the apostle, saint; Bible. N.T. -- criticism, interpretation, etc